Public disclosure, risk, and performance at bank holding companies - Beverly Hirtle (Federal Reserve Bank of New York, 2007)
This paper examines the relationship between the amount of information disclosed by bank holding companies (BHCs) and their subsequent risk profile and performance. Using data from the annual reports of BHCs with large trading operations, we construct an index of publicly disclosed information about the BHCs' forward-looking estimates of market risk exposure in their trading and market-making activities. The paper then examines the relationship between this index and the subsequent risk and return in both the BHCs' trading activities and the firm overall, as proxied by equity market returns. The key findings are that more disclosure is associated with lower risk, especially idiosyncratic risk, and in turn with higher risk-adjusted returns. These findings suggest that greater disclosure is associated with more efficient risk taking and thus improved risk-return trade-offs, although the direction of causation is unclear.
Keywords: G21; G32; G28; 330; disclosure; value at risk; market discipline; banking; Bank; Publizitätspflicht; Risikomaß; USA